Study on stress wave propagation and failure characteristics of key parts in tunnel under blasting load - Jichao Duan; Qi Zong; Haibo Wang; Bing Cheng; Pengfei Gao (Scientific Reports, 2024)
Abstract To investigate the propagation mechanisms of stress waves and the characteristics of crack distribution in tunnel structures subjected to explosive effects, an experimental model simulating rock mass using cement mortar was employed. Blasting experiments were conducted at various vertical locations relative to the tunnel. Utilizing ultra-dynamic strain monitoring alongside high-speed digital image recognition, we captured in real time the dynamic evolution of stress waves as well as the precise initiation and expansion paths of cracks. A comprehensive analysis was performed on both stress wave propagation and damage patterns within the refuge structure. Furthermore, the reliability of our numerical simulation algorithm was validated through an examination of fluid-structure coupling algorithms. The results indicated that peak strains at monitoring points within the tunnel increased as detonation points approached it, leading to heightened structural damage. Numerical simulations demonstrated a strong correlation between observed peak strains at critical locations and corresponding damage data from our experimental model. Additionally, it was found that decreasing height between detonation points and the tunnel resulted in increased dynamic response parameters—such as overpressure, velocity, and acceleration—at monitoring sites within the tunnel, thereby exacerbating damage to key areas including vaults and footwall structures. To mitigate potential structural instability within refuges, a full-section molded concrete lining support system was implemented along with supplementary anchor (mesh) spraying in critical regions to ensure long-term operational safety.